The Relationship Marketing Performance Evaluating in Financial Services Sector of Project Management - Mohammad Reza Rostami; Hamideh Mirshahi (Shock and Vibration)
In any economy, the financial sector is interpreted as the driving force in the process of achieving growth through the appropriate and optimal allocation of resources to productive economic sectors. Financial institutions are defined as customer service providers. The generalization of the obtained results to the whole statistical population is the last step in this research. The research is a survey that can provide data on attitudes, feelings, beliefs, past behaviors, recorded behaviors, and the recognition of the acquisition of personal characteristics. Considering that the services available in commercial banks are relatively the same and it is difficult for most banks to differentiate these services from competitors, therefore, many banks around the world have tended to use the relationship marketing approach. The concept of relationship marketing was first mentioned in the American marketing literature in a 1983 article by Barry, who considered relationship marketing as a strategy for attracting, retaining, and strengthening customer relationships. This means that if the bank’s reciprocal relationships increase by 1 unit, it is 95% likely that the value of customer satisfaction with financial services will increase by 0.663 units. Factor loads also have a very good quality in explaining their construct because they have a value of more than 5%. On the other hand, the value of the t significance coefficient for the relationship between the variables of the bank’s reciprocal relationships and customer satisfaction with financial services is 8.471 at the 95% confidence level, which is more than 1.96, indicating the importance of the bank’s reciprocal relationships on customer satisfaction with financial services. To evaluate the sixth hypothesis that “the bank’s reciprocal relationships affect customer satisfaction with financial services,” factor load and significance coefficient obtained from structural equation modeling were used. Considering the path coefficient related to this hypothesis, it can be concluded that the bank’s reciprocal relationships with the value of 0.663 affect customer satisfaction with financial services.